FACTORS INFLUENCING FARMERS DECISION IN COMMUNITY-BASED FOREST MANAGEMENT PROGRAM, KPH CIAMIS, WEST JAVA - Ary Widiyanto (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2019)
Community Based Forest Management program through Pengelolaan Hutan Bersama Masyarakat (PHBM) scheme has been implemented in Perhutani forest in Java since 2001. The program has been developed to alleviate rural poverty and deforestation as well as to tackle illegal logging. However, there was very limited information and evaluation on activities of the program available especially in remote area/regencies, including Ciamis. This paper studies the socio-economic, geographical and perceptional factors influencing farmers decision to join PHBM program, farmers selection criteria for the crops used in the program, and farmer decision to allocate their time in the program. It also examines the costs and income related to the program and how the program land was allocated between different farmers groups and within the farmers groups as well as the perceptions of the state company’s (Perhutani) staff members on the program. Deductive approach was used with quantitative and qualitative methods. Quantitative data were collected through questionnaires from 90 respondents at three farmer groups from 3 villages, 30 respondents of each group respectively. Cross tabulation and descriptive statistical analysis were used to analyse quantitative data. Qualitative data were collected through interviewing of 9 key informants, three informants of each farmer group respectively, and two Perhutani’s staff. Results showed that PHBM program contributed to about 26.9% to community’s monthly income. The program introduced benefit-sharing system and accommodated community initiatives. Perhutani’s support was illustrated by freedom of choice of community in selecting the sharing area (land allocated for farmer to manage) and the planted crops. Factor influencing farmers’ decision in selecting the sharing area was geographic conditions, in selecting the crops was farmer skills, and in allocating working time was farmers’ priority.